Bile acid-activated receptors and the regulation of macrophages function in metabolic disorders. (August 2020) - Fiorucci, Stefano; Baldoni, Monia; Ricci, Patrizia; Zampella, Angela; Distrutti, Eleonora; Biagioli, Michele
Graphical abstract: Abstract : Bile acids are produced in the liver by the cholesterol breakdown and further metabolized by the intestinal microbiota to generate a group of chemically heterogeneous steroids that bind and activate a family of cells surface and nuclear receptors, collectively known as the bile acid-activated receptors (BARs). The two best characterized members of this family are the farnesoid-x-receptor (FXR) and G protein Bile Acid Receptor (GPBAR1). Both receptors are expressed by cells of innate immunity including liver-resident and intestinal-resident macrophages and monocytes-derived macrophages. Because FXR and GPBAR1 knockout mice are biased toward a pro-inflammatory phenotype, it appears the both receptors might have a role in the development and maintenance of a tolerogenic phenotype. FXR and GPBAR1 ligands have been proven effective in the treatment in inflammatory and metabolic disorders and ligands for these receptors are currently under development for the treatment of non-alcoholic steato-hepatitis and diabetes.